Sex differences in glutamate AMPA receptor subunits mRNA with fast gating kinetics in the mouse cochlea - Lozier, Nicholas R.; Muscio, Steven; Pal, Indra; Cai, Hou-Ming; Rubio, María E. (Frontiers in Systems Neuroscience, 2023)
Evidence shows that females have increased supra-threshold peripheral auditory processing compared to males. This is indicated by larger auditory brainstem responses (ABR) wave I amplitude, which measures afferent spiral ganglion neuron (SGN)-auditory nerve synchrony. However, the underlying molecular mechanisms of this sex difference are mostly unknown. We sought to elucidate sex differences in ABR wave I amplitude by examining molecular markers known to affect synaptic transmission kinetics. Alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) mediate fast excitatory transmission in mature SGN afferent synapses. Each AMPAR channel is a tetramer composed of GluA2, 3, and 4 subunits (Gria2, 3, and 4 genes), and those lacking GluA2 subunits have larger currents, are calcium-permeable, and have faster gating kinetics. Moreover, alternatively spliced flip and flop isoforms of each AMPAR subunit affect channel kinetics, having faster kinetics those AMPARs containing Gria3 and Gria4 flop isoforms. We hypothesized that SGNs of females have more fast-gating AMPAR subunit mRNA than males, which could contribute to more temporally precise synaptic transmission and increased SGN synchrony. Our data show that the index of Gria3 relative to Gria2 transcripts on SGN was higher in females than males (females: 48%; males: 43%), suggesting that females have more SGNs with higher Gria3 mRNA relative to Gria2. Analysis of the relative abundance of the flip and flop alternatively spliced isoforms showed that females have a 2-fold increase in fast-gating Gria3flop mRNA, while males have more slow-gating (2.5-fold) of the flip. We propose that Gria3 may in part mediate greater SGN synchrony in females. Significance Statement: Females of multiple vertebrate species, including fish and mammals, have been reported to have enhanced sound-evoked synchrony of afferents in the auditory nerve. However, the underlying molecular mediators of this physiologic sex difference are unknown. Elucidating potential molecular mechanisms related to sex differences in auditory processing is important for maintaining healthy ears and developing potential treatments for hearing loss in both sexes. This study found that females have a 2-fold increase in Gria3 flop mRNA, a fast-gating AMPA-type glutamate receptor subunit. This difference may contribute to greater neural synchrony in the auditory nerve of female mice compared to males, and this sex difference may be conserved in all vertebrates.